Arahan Pengembangan Permukiman Suku Bajo di Wilayah Pesisir Kelurahan Bajoe, Kabupaten Bone - Yola Amalia Ayuningsih; Shirly Wunas; Mimi Arifin (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Bajo tribe is in the Bugis tribe community that grows and develops in the coastal area of ​​Bone Regency, forming a dense residential area with a very strong kinship. The purpose of this study, (1) identify the conditions of settlement development (2) explain the settlement service facilities and transportation infrastructure and (3) describe the direction of settlement development based on settlement service facilities and the Bajo Tribe community transportation infrastructure. This research uses a descriptive qualitative approach. Data collection techniques used are primary data through field surveys (questionnaires, interviews and observations) and secondary data through international surveys (government) and literature studies. The results showed the basic service facilities in the Bajo tribal settlement had fulfilled the standard for livable housing planning, but it was not sufficient from the supporting facilities for its service activities. Road network infrastructure in residential areas has met the accessibility index, but it is not yet adequate from the aspect of connectivity to loading and unloading activities of fish catches. Directions for the development of settlements based on settlement service facilities and transportation infrastructure of the Bajo tribe, namely boat moorings are directed to build docks with simple construction and development of facilities such as fish auction sites so that the quality of the catches is maintained and the sale value can be in accordance with general market prices, and fish drying places integrated with the construction of under the stage house can be equipped with solar energy systems.